SOCIAL NORMS AND VALUES OF ITALIAN-AMERICAN MAFIA AS PORTRAYED IN MARIO PUZO’S THE GODFATHER - MUALIM, ILHAM ROMADHON (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: The Godfather, Social Norms and Values, Italian-American Mafia,Sociological ApproachSociety refers to a group of people who share common area, culture and behavior patterns. Society is a mixture of subcultures in which different societies from different parts of the world preserve their original cultures. The Godfather describes how Vito Corleone as the leader of Corleone family tries to elevate the importance of Social Norms and Values of Italian-American Mafia which are based on the traditional Italian Mafia to the members of his Mafia family.The application of Sociological approach used in this study is to figure out what are the social norms and values of Italian-American Mafia community and how important they are to the members of Mafia. Furthermore, it is used to explore the structure of Italian-American Mafia organization. The data are collected from the narration, characterization, and the dialogue of the characters. The procedure of analysis comprises of collecting data, interpreting and analyzing related object of the study in the story, and drawing the conclusion.The result of the study shows the importance of Social Norms and Values of Italian-American Mafia and the consequences for those who do not obey the rules of this community. Various punishments as a result for a member who fails to obey the rules of Mafia community are clearly described in the novel. Hopefully, a study about social norms and values can be used to help other researchers who want to analyze the sequel novel of The Godfather which is entitled The Sicilian by using the same perspective.